Proventricular dilatation disease (PDD) outbreak in blue-and-gold macaws (Ara ararauna) in the State of Santa Catarina, southern Brazil1 - de Araujo J.L. (2017)
© 2017 Pesq. Vet. Bras.Proventricular dilatation disease (PDD) is a lethal and important disease of captive psittacinebirds, and affects a wide range of species, including endangered ones, and lacks aneffective treatment. This report describes PDD in three blue-and-gold macaws (Ara ararauna)in southern Brazil. All three macaws originated from the same aviary and presentedsimilar clinical signs including anorexia, apathy, emaciation and prostration. At necropsy,one of the macaws presented an enlarged proventriculus. Histologically, lymphoplasmacyticinfiltrates was observed in the ganglia and nerves of the esophagus, crop, proventriculus,ventriculus, heart, adrenal glands, and adrenal medulla of all three cases. Twomacaws had meningoencephalomyelitis and one had myocarditis. Immunohistochemistryidentified PaBV antigen in the brain, proventricular, ventricular ganglia, and epicardial ganglia,and cardiomyocytes of all three macaws.